Association between hypertension and cutaneous melanoma, and the effect of aspirin: extended follow-up of a large randomised controlled trial. (August 2022) - Yan, Mabel K.; Orchard, Suzanne G.; Adler, Nikki R.; Wolfe, Rory; McLean, Catriona; Rodríguez, Luz María; Woods, Robyn L.; Gibbs, Peter; Chan, Andrew T.; Haydon, Andrew; Mar, Victoria J.
Abstract: Background: The association between hypertension and melanoma is unclear, and previous analyses of data from the ASPirin in Reducing Events in the Elderly (ASPREE) study demonstrated a reduced number of invasive melanoma events amongst aspirin-exposed hypertensive individuals. Methods: Data from the ASPREE study which included (1) the intervention period with a median follow-up of 4.7 years, and (2) the observational period with an additional 2 years follow-up, were combined for this analysis. Logistic regression analyses examined the association between baseline hypertension and treatment status and past melanoma history. Survival analyses examined the association between hypertension and melanoma risk, and the effect of aspirin across hypertension groups. Cox proportional hazards models were used to compare incidence across groups. Results: 19, 114 participants (median age of 74 years) were randomised to daily 100 mg aspirin or placebo. At baseline, hypertension and past melanoma history were recorded in 14, 195 and 685 individuals, respectively. After adjustment for confounders, hypertension was significantly associated with past melanoma history (OR=1.34, 95%CI: 1.11–1.62). In a prospective analysis, baseline hypertension was not associated with melanoma risk. However, aspirin was associated with a reduced risk of incident melanoma amongst individuals with uncontrolled hypertension (blood pressure ≥140/90 mmHg; HR=0.63, 95%CI 0.44–0.89), but not in those with controlled hypertension (HR=1.04, 95%CI 0.74–1.46). Conclusion: Our results support a reduced melanoma incidence amongst individuals with uncontrolled hypertension exposed to aspirin. Additional studies are required to confirm these findings. Highlights: Aspirin may reduce incident melanoma risk in uncontrolled hypertensives. High-risk groups who may benefit from aspirin chemoprevention need exploration. The association between hypertension and melanoma warrant further investigation.